Direct to implant breast reconstruction with biological acellular dermal matrices. (2nd March 2020) - Teoh, Victoria; Gui, Gerald
Abstract : Breast cancer is the most commonly diagnosed female cancer in the UK, with one in eight women receiving a cancer diagnosis during their lifetime. Forty per cent of women diagnosed with breast cancer undergo mastectomy as their primary therapeutic procedure. While a full range of choices is offered, breast reconstruction using implants is the patient-preferred method of reconstruction following mastectomy. This review discusses the evolution of implant-based reconstruction, focusing on the recent trend towards prepectoral breast reconstruction. Key quality indicators in the current literature are considered, including oncological outcomes, aesthetics and patient-related outcome measures, as are the health-care economics of this emerging surgical technique.